MEME KİTLELERİNİN DEĞERLENDİRİLMESİNDE NÜKLEER TIP YAKLAŞIMI - ERDOĞAN, Serpil (Cerrahpaşa Medical Journal, 2014)
Background.- In the developing countries, the incidence of breast cancer, which is the major public health problem, is rising in the population with changes more marked in younger women. Physical examination and many different diagnostic techniques are used to evaluate sings and symptoms of breast cancer. Mammography is the most effective method of detecting early breast cancer which is not clinically palpable. However, mammography gives “indeterminate” results especially in the breast with dens tissue. The only definitive means of confirmation of the lesion seen on mammography is histologic examination of tissue. A non-invasive technique to select those who would benefit most from breast biopsy and reduce the number of negative biopsies would clearly be of value. Scintimammography is a non-invasive technique employing various radionuclides to diagnose patients with breast cancer. Mammoscintigraphy done with Ga67, Tc99m-MDP and labelled somatostatin analogs are not routinely used for the evaluation of breast cancer while they have a historical value. F-18-FDG-PET study is more valuable than the other imaging techniques because of not only being eligible to show primary tumour but also axillary lymph nodes. However, high cost and lack of availability of PET in every nuclear medicine department restrict its use in this patient population. Tc99m-MIBI mammoscintigraphy, on the other hand, is continuing to save its value as a screening technique as it has high sensitivity and improves the specificity of mammography for the detection of breast cancer.